2014
DOI: 10.1038/nrcardio.2014.161
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in bicuspid anatomy

Abstract: Transcatheter aortic valve implantation (TAVI) is an established therapeutic option for high-risk patients with tricuspid aortic valve stenosis. Historically, the presence of a bicuspid aortic valve (BAV) has been regarded as a contraindication to TAVI, on the basis of putative concerns about the associated risks of elliptical deployment, accelerated leaflet degeneration, periprosthetic leaks, and aortic complications. Fortunately, with technological refinements and mounting experience, reasonable success has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 49 publications
0
41
1
Order By: Relevance
“…Yousef et al (27) and Mylotte et al (26) separately reported the rates of paravalvular leak of 2+ or greater as 30.8% and 28.4% respectively. TAVI used in Asian patients with bicuspid valve stenosis has yielded satisfactory outcomes when compared to Western patients (29,30). China reported unusually high prevalence of bicuspid aortic valve in Chinese patients with severe aortic valve stenosis and these patients were associated with high leaflet calcium burden.…”
Section: Discussionmentioning
confidence: 99%
“…Yousef et al (27) and Mylotte et al (26) separately reported the rates of paravalvular leak of 2+ or greater as 30.8% and 28.4% respectively. TAVI used in Asian patients with bicuspid valve stenosis has yielded satisfactory outcomes when compared to Western patients (29,30). China reported unusually high prevalence of bicuspid aortic valve in Chinese patients with severe aortic valve stenosis and these patients were associated with high leaflet calcium burden.…”
Section: Discussionmentioning
confidence: 99%
“…Recent multicentre Bic-AV registry revealed that the rate of procedural success rate was relative high (89.5%) and survival was similar to that in patients with a tricuspid AV who undergo TAVI. Nevertheless, moderate or severe AR and aortic dissection seem to occur more frequently (28.3%) in patients with Bic-AV than tricuspid aortic valve [11]. However, it is notable that in a small TEE series valve expansion appeared relatively circular on in all cases, suggesting that a Bic-AV does not necessarily preclude symmetric expansion of a balloon-expandable valve with sufficient radial strength.…”
Section: Tavi In Bicuspid Aortic Valve (Bic-av)mentioning
confidence: 81%
“…Careful navigation and deflection of the TAVI system away from walls of the aortic arch and the ascending aorta during catheter passage is recommended in these high-risk patients. -Conduction abnormalities: an asymmetrical calcium distribution, with deposits located in the noncoronary cusp or valve oversizing, compared to an elliptical BAV orifice, increase the risk of new pacemaker implantation [36]. Current registry data provide guidance for the transcatheter treatment of this challenging group of patients.…”
Section: Bicuspid Aortic Valvementioning
confidence: 99%